I came a stranger : the story of a Hull-House girl - Polacheck, Hilda Satt, 1882-1967.; Epstein, Dena J., 1916-2013. (Urbana : University of Illinois Press, 1989)
Biography of Hull-House activist and writer.
pt. I.A Polish Childhood, 1882-92: memories of Poland -- pt. II. The voyage to American: a new life begins, 1892-95: the voyage to America -- Transplanted -- South Halsted Street -- My father -- My mother -- pt. III. Growing up with Hull-House, 1895-1912: I discover Hull-House -- A funeral -- My first job -- Growing up -- The oasis in the desert -- The west side Turner Hall -- The university -- New horizons -- Jane Addams -- New horizons [II] -- The forward movement -- The walking delegate -- pt. IV. Family life and politics in Milwaukee, 1912-29: Milwaukee -- War -- Peace -- Woman's suffrage -- Women's International League for Peace and Freedom -- December 1927 -- pt. V. Return to Chicago, 1929-35: going back to Chicago -- WPA -- May 1935.
Includes bibliographical references and index.
Description based on online resource; (viewed 2020-05-15).
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
JSTOR
Keywords: Polacheck, Hilda Satt, -- 1882-1967.; Hull-House (Chicago, Ill.) -- History; Polacheck, Hilda Satt, -- 1882-1967.; Hull-House (Chicago, Ill.); Jews -- Illinois -- Chicago -- Biography; Chicago (Ill.) -- History; Women -- United States -- History -- 20th century; Women social reformers -- United States -- Biography; Juifs -- Illinois -- Chicago -- Biographies; Chicago (Ill.) -- Histoire; Femmes -- États-Unis -- Histoire -- 20e siècle.; Réformatrices sociales -- États-Unis -- Biographies; Jews; Social reformers; Women; Women social reformers; Illinois -- Chicago; United States; Autobiografie; 1900-1999; Polacheck, Hilda S; Biographies; History